BORLAND C++ BUILDER PROGRAMMALASTIRIW TILINIŃ GRAFIKALIQ IMKANIYATLARINAN PAYDALANIW - Kalxanov, P.J.; Orınbaev, A.A. (ILIM hám JÁMIYET, 2022)
This article is written about working with graphics using classes, properties and functions of Borland C++ Builder components. Borland C++ Builder is a powerful visual object-oriented programming system that allows you to create various graphic shapes. C++ Builder can be used anywhere with the extended C++ language standard to enhance existing applications, improve performance, and provide a professional user interface.